2019
DOI: 10.22207/jpam.13.4.50
|View full text |Cite
|
Sign up to set email alerts
|

Study the Probiotic Properties of Pediococcus pentosaceus Isolated from Fish Ponds in Basra City, South of Iraq

Abstract: Citation: Raghad S. Jaafar, Fadhil N. Al-knany, Bayan A. Mahdi and Asaad M.R. Al-Taee, Study the Probiotic Properties of Pediococcus pentosaceus AbstractOne of the most important problems to the fish in aquaculture is pathogenic bacteria. Therefore, is a serious necessity in aquaculture to upgrade microbial hegemony strategies. The present study focused on isolation, screening, biochemical and molecular level characterizations of potential probiotic bacteria from the fish pond in Basra city southern Iraq. Isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Several bacteria from the genera Bacillus , Lactobacillus and Lactococcus have been successfully isolated from the intestine of healthy fish and are known as the main groups of probiotic bacteria in aquaculture (Balcázar et al, 2006; Irianto & Austin, 2002; Ringø & Gatesoupe, 1998). Recent studies, however, have revealed new potential isolates, such as bacteria from the genera Staphylococcus (Kanjan & Sakpetch, 2020; Rajeswari et al, 2016), Enterococcus (Dias et al, 2019) and Pediococcus (Jaafar et al, 2019; Xing et al, 2013). As knowledge about emerging species of fish of economic interest continues to advance, different strains with promising probiotic activity are being described.…”
Section: Introductionmentioning
confidence: 99%
“…Several bacteria from the genera Bacillus , Lactobacillus and Lactococcus have been successfully isolated from the intestine of healthy fish and are known as the main groups of probiotic bacteria in aquaculture (Balcázar et al, 2006; Irianto & Austin, 2002; Ringø & Gatesoupe, 1998). Recent studies, however, have revealed new potential isolates, such as bacteria from the genera Staphylococcus (Kanjan & Sakpetch, 2020; Rajeswari et al, 2016), Enterococcus (Dias et al, 2019) and Pediococcus (Jaafar et al, 2019; Xing et al, 2013). As knowledge about emerging species of fish of economic interest continues to advance, different strains with promising probiotic activity are being described.…”
Section: Introductionmentioning
confidence: 99%